A study on the reasonable dietary trajectory of elderly people in the community and its correlation with body mass index - Liu, Mengya; Chang, Yuqing; Guo, Wenjing; Zhao, Siyi; Zhang, Meng; Ma, Xiaoyan; Ji, Xiaomei; Liu, Youran; Zhang, Li (Frontiers in Nutrition, 2024)
Objective To explore the reasonable dietary trajectory of elderly people in the community and to test the correlation between different dietary trajectories and BMI of the elderly people in the community to provide a reference for these individuals to formulate scientific interventions and cultivate healthy living habits.The data of The Chinese Longitudinal Healthy Longevity Survey from 2011 to 2018 were used to evaluate the dietary status of elderly people in the community according to their diet, and body mass index was calculated according to height and weight. The latent variable growth mixed (LGMM) model was used to analyze the development trajectory of diet in elderly people, and the multivariate logistic regression model was used to test the relationship between different dietary development trajectories and BMI changes as well as to test the correlation between different dietary trajectories and BMI of the elderly people in the community.The LGMM fit four dietary trajectories of elderly individuals: the continuous reasonable diet group (37.81%), the dietary behavior decline group (28.84%), the continuous unreasonable diet group (20.16%), and the dietary behavior improvement group (13.19%). The results showed that factors including male sex, rural setting, being spouseless, nonformal education status, not being wealthy, living alone, and having tooth loss were more likely to be classified as the "persistently unreasonable diet group" (P<0.05). The logistic regression results showed that the "continuous reasonable diet group" and the "dietary behavior improvement group" were significantly correlated with the development of obesity to a normal BMI.The dietary behavior of the elderly was significantly correlated with BMI value, and improving the reasonable dietary behavior of the elderly could reduce the high BMI to the normal range, but could not restore the low BMI to the normal range, indicating that reasonable dietary behavior is an important measure to prevent and improve overweight or obesity in the elderly. There is significant heterogeneity in the dietary behavior , and community medical staff should identify the risk factors of various dietary behaviors of other groups as soon as possible, and provide corresponding intervention strategies to help them change their poor dietary behaviors and improve nutritional status.